Firm selection and growth in carbon offset markets: Evidence from the Clean Development Mechanism - Qiaoyi Chen; Nicholas Ryan; Daniel Yi Xu (Yale University, Economic Growth Center, 2025)
We study carbon offsets sold by firms in China under the Clean Development Mechanism (CDM). We find that offset-selling firms, meant to cut carbon emissions, instead increase them by 49% after starting an offset project. In a model of firm investment decisions and offset review, we estimate that CDM firms increase emissions due to both the selection of higher-growth firms into projects (35 pp) and because offset projects themselves boost firm growth and therefore emissions (14 pp). The CDM reduces global surplus by causing damages from increased emissions four times greater than private gains from trade in the offset market.
Keywords: 330